2022
DOI: 10.1007/s13300-022-01296-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit of Switching from Low-Dose to High-Dose Empagliflozin in Patients with Type 2 Diabetes

Abstract: Introduction: Sodium-dependent glucose cotransporter 2 (SGLT2) inhibitors ameliorate blood glucose levels in patients with type 2 diabetes mellitus (T2DM) by inhibiting the reabsorption of glucose from the kidneys, thus increasing urinary glucose excretion. Most SGLT2 inhibitors have been reported to exert dose-dependent effects. However, little is known about the benefits of increasing the dose of SGLT2 inhibitors in clinical use. The aim of the present study was to investigate the effect of increasing the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In addition, Matsumura et al reported that baseline DBP and TG were independent predictors of HbA1c decrement [6]. In the present study, DBP was also significantly higher in the dose-escalation group at baseline, and differences in patient backgrounds may have contributed to the decrease in HbA1c in the doseescalation group.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In addition, Matsumura et al reported that baseline DBP and TG were independent predictors of HbA1c decrement [6]. In the present study, DBP was also significantly higher in the dose-escalation group at baseline, and differences in patient backgrounds may have contributed to the decrease in HbA1c in the doseescalation group.…”
Section: Discussionsupporting
confidence: 58%
“…A meta-analysis of 51 randomized clinical trials involving 23,989 patients with T2DM has reported that empagliflozin, dapagliflozin, and canagliflozin significantly decreased regulated glycemia, BW, BP, and HDL in a dose-dependent manner [5]. A retrospective study involving empagliflozin administration six months after dose escalation showed significant decrements in BW, BMI, γ-GTP, TG, FPG, and HbA1c in type 2 diabetic patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the observational REAL-WECAN study published by our group, patients who intensified their antihyperglycemic therapy by switching to CANA300 from other SGLT-2is (also including CANA100) showed similar results to those observed in the present study [ 15 ]. However, in a recent RWS evaluating the intensification of another SGLT-2i, empagliflozin, from 10 mg to 25 mg, the HbA1c and weight reductions at 24 weeks were only −0.13% and −0.6 kg, respectively [ 21 ]. Both RCTs and RWS suggest greater effectiveness of CANA300 within the SGLT-2i class, and intensification to the higher dose of canagliflozin could delay the need to add new drugs and therefore avoid an increase in treatment burden.…”
Section: Discussionmentioning
confidence: 99%